Formulation and evaluation of thin film nanoemultion from rose flower ethanol extract (rosa hybrida hort.) and antidiabetes mellitus type 2 activity test using in vitro enzyme - Gustana, Erick Kurniawan; Jafar, Garnadi; Aligita, Widhya; Nurfaiza, Putri; Hanaya, Cicia Rosa; Salsabilla, Syifa (Institute of Computer Science (IOCS), 2025)
Diabetes mellitus is a chronic disease with a rising global prevalence. Natural antidiabetic agents derived from plant bioactive compounds offer a promising therapeutic alternative. Rose flowers (*Rosa hybrida Hort*) contain flavonoids such as kaempferol, known for their antidiabetic activity. However, poor solubility and bioavailability limit their therapeutic potential. This study aimed to develop and characterize a nanoemulsion of rose flower extract to enhance the stability and bioavailability of its active compounds. The extract was obtained by maceration using 96% ethanol and analyzed using Liquid Chromatography Tandem Mass Spectrometry (LC-MS/MS). Nanoemulsion formulations were developed using various types and concentrations of nonionic surfactants. Characterization included particle size, polydispersity index (PDI), zeta potential, and morphology. The optimal nanoemulsion showed a particle size <300 nm, PDI <0.5, and zeta potential around ±20 mV, indicating good stability. Transmission Electron Microscopy (TEM) revealed uniformly distributed spherical globules. LC-MS/MS confirmed the presence of kaempferol as the main active compound. The formulated nanoemulsion was successfully incorporated into an oral thin film, exhibiting favorable characteristics such as appropriate particle size, PDI, zeta potential, morphology, and satisfactory evaluation results including organoleptic properties, moisture content, pH, weight uniformity, film thickness, folding endurance, and disintegration time.